Sistem Pendukung Keputusan Calon Penerima Beasiswa Yayasan Politeknik Kesehatan Bhakti Setya Indonesia Menggunakan Metode SAW Dan TOPSIS - Senoaji, Muhammad Senoaji Wibowo; Enny Itje Sela; Apriyaldi Lukman; Ferryma Arba Apriansyah; Olwin Kirab Novaldy (Politeknik Piksi Ganesha Indonesia, 2024)
The scholarship selection system at the Bhakti Setya Indonesia Health Polytechnic Foundation is still conducted manually, making it less transparent and time-consuming. This process requires an objective and measurable method to ensure fairness in determining scholarship recipients. This study aims to develop a decision support system for scholarship selection using the Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The SAW method calculates scores based on the aggregation of weighted normalized values, while the TOPSIS method evaluates candidates based on their proximity to ideal solutions. The criteria used in this study include parental income, number of dependents, GPA, organizational involvement, and achievements. The results indicate that the developed system is capable of ranking candidates with high accuracy. Candidates with the best performance consistently ranked at the top in the results of both methods.